Attributes and factors associated with long covid in patients hospitalized for acute COVID-19: A retrospective cohort study. - Bethlehem Berhanu Minassie; Wondwossen Amogne Degu; Eyob Kebede Etissa; Natnael Fitsum Asfeha; Salem Taye Alemayehu; Dawit Kebede Huluka (PLoS ONE)
Background It is now recognized that many patients have persistent symptoms after recovery from acute COVID-19 infection, an infection caused by the coronavirus SARS-CoV-2. This constellation of symptoms known as 'Long COVID' may manifest with a wide range of physical and cognitive/psychological symptoms. Few data are available on the prevalence, attributes, and factors associated with Long COVID in Africa. Method This was a retrospective review of patients' electronic medical records from Hallelujah General Hospital (one of the first private hospitals to treat COVID-19 patients). The hospital's database was searched for patients hospitalized for acute COVID-19 infection from March 2020 to December 2022. Two hundred and forty-seven participants who underwent follow-up beginning four weeks after symptom onset were assessed for Long COVID. Admission and follow-up data were collected using Kobo Toolbox and exported into SPSS 27 for analysis. The relationship between the independent and dependent variables was explored through binary logistic regression. Results One hundred seventy-eight (72.1%) participants had at least one persisting symptom 4 weeks post-symptom onset, at a median follow-up time of 35 (IQR 32-40) days. The most frequently reported symptoms were fatigue (41.7%), shortness of breath (31.2%), cough (27.1%), and sleep disturbances (15%). Duration of symptoms more than 7 days before admission [aOR = 1.97; CI95% = 1.04 to 3.75; P = 0.038] and length of stay more than 10 days in the hospital [aOR = 2.62; CI95% = 1.20 to 5.72; P = 0.016] were found to be significantly associated with Long COVID. Conclusion There is a high prevalence of Long COVID among patients hospitalized for acute COVID-19. Those who had a longer duration of symptoms before admission and a longer stay in the hospital appear to have a higher risk.